Social capital and factors associated with the caries experience in adults - a population-based study in Brazil - Jamille Silva NOGUEIRA; Antonio Carlos PEREIRA; Antonio Carlos FRIAS; Gláucia Maria Bovi AMBROSANO; Karine Laura CORTELLAZZI; Luciane Miranda GUERRA; Denise de Fátima Barros CAVALCANTE; Jaqueline Vilela BULGARELI (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract The objective of this study was to investigate the experience of caries related to social capital and associated factors in adults in large-scale population-based study. A Cross-sectional study was performed in 163 municipalities in the State of São Paulo, Brazil (SBSP-2015). 17,560 people were evaluated, of which 6051 were adults aged 35-44 years. Hierarchical logistic regression analysis was proposed. Outcome variables (decayed teeth, missing teeth and DMFT) and independent variables were included in the model, considering the distal (income and schooling); intermediate (social capital) and proximal levels (sex and ethnicity). Results showed that income up to 1,500 reais - US$ 367.6 in 11/11/2019 - (OR = 1.91;1.75-2.08), schooling up to 8 years (OR = 1.32;1.12-1.56) and non-white ethnicity (OR = 1.54;1.35-1.76) were more likely to have decayed teeth. Income up to 1500 reais (OR = 1.29;1.15-1.44), schooling up to 8 years (OR = 2.13;1.90-2.38), low social capital (OR = 1.84;1.65-2.04), medium social capital (OR = 1.15;1.01-1.30) and females were more likely to have lost teeth (OR = 1.13;1.03-1.23). Schooling up to 8 years (OR = 1.51;1.35-1.69), low social capital (OR = 1.25; 1.14-1.37) and female (OR = 1.40,1.19-1.53) were associated with DMFT. It was concluded that sociodemographic factors and low social capital were associated with the experience of caries, which should be taken into account in the formulation of public policies.